2008
DOI: 10.1113/jphysiol.2008.159665
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐carotid hyperosmotic stimulation increases Fos staining in forebrain organum vasculosum laminae terminalis neurones that project to the hypothalamic paraventricular nucleus

Abstract: Body fluid hyperosmolality has long been known to elicit homeostatic responses that range from drinking to inhibition of salt appetite to release of neurohypohyseal hormones (i.e. vasopressin and oxytocin). More recently, it has been recognized that hyperosmolality is capable of also provoking a significant increase of sympathetic nerve activity (SNA). It has been reported that neurones in the forebrain organum vasculosum laminae terminalis (OVLT) and hypothalamic paraventricular nucleus (PVN) each contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 70 publications
(164 reference statements)
1
49
1
1
Order By: Relevance
“…Importantly, it has already been demonstrated that the vasoconstrictive effects produced by stimulation of the entire AV3V region have origins in the OVLT (23) that, in turn, is activated after elevation of central osmolality (33) increasing sympathetic activity (34). Recent results in anesthetized rats (1) drinking 0.9% NaCl have suggested that neurons from forebrain areas, such as OVLT influence the excitability of the rostral ventrolateral medulla (RVLM), one of the most important areas for the cardiovascular control (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, it has already been demonstrated that the vasoconstrictive effects produced by stimulation of the entire AV3V region have origins in the OVLT (23) that, in turn, is activated after elevation of central osmolality (33) increasing sympathetic activity (34). Recent results in anesthetized rats (1) drinking 0.9% NaCl have suggested that neurons from forebrain areas, such as OVLT influence the excitability of the rostral ventrolateral medulla (RVLM), one of the most important areas for the cardiovascular control (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that like increases in central osmolality, increased plasma ANG II is sensed by the OVLT, and this activation also is important for chronic cardiovascular regulation. Also, because OVLT cells are responsive to increases in central osmolality (33,34), as well as ANG II (4,32), it is likely that the OVLT is a crucial site in the forebrain that contributes to hypertension induced by a combination of salt and ANG II, a currently well-reviewed concept in the field of neurogenic hypertension (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies (54,55), hypertonic saline increases SNA and MAP through a mechanism that depends largely on neurons of the forebrain organum vasculosum laminae terminalis, which an anatomic study (19) has shown to send mostly glutamatergic projections to downstream sympathetic control regions of the PVN. It should be acknowledged that the exaggerated LSNA response to hypertonicity observed in CIHexposed rats could have arisen from the recruitment of PVNindependent sympathoexcitatory mechanisms or neural pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In separate groups of sham (n ϭ 9) and CIH-exposed (n ϭ 9) rats, osmotic-sensitive regions of the forebrain were stimulated as previously described (6,54,55,58,59). Briefly, warmed (37°C) aqueous solutions of isotonic (290 mosM) and hypertonic (870 mosM) saline (NaCl) were delivered in a volume of 100 l over 10 -15 s through a flame-pulled fine-tipped catheter (PE-50 tubing) inserted into the internal carotid artery (ICA).…”
Section: Internal Carotid Artery Injections Of Hypertonic Salinementioning
confidence: 99%